2012
DOI: 10.1007/s00268-012-1544-x
|View full text |Cite
|
Sign up to set email alerts
|

Is There any Benefit from Expanding the Criteria for the Resection of Hepatocellular Carcinoma in Cirrhotic Liver? Experience from a Developing Country

Abstract: RF-assisted sequentional "coagulate-cut liver resection technique" may be a viable alternative for management of patients with advanced HCC in cirrhotic liver with impaired function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Radiofrequency-assisted sequential “coagulate-cut” liver resection technique was performed in all patients who underwent liver resection. 35 , 36 Type of liver resection was defined according to Brisbane Terminology of liver anatomy and resections. 37 Major liver resection was defined as resection of three or more liver segments.…”
Section: Methodsmentioning
confidence: 99%
“…Radiofrequency-assisted sequential “coagulate-cut” liver resection technique was performed in all patients who underwent liver resection. 35 , 36 Type of liver resection was defined according to Brisbane Terminology of liver anatomy and resections. 37 Major liver resection was defined as resection of three or more liver segments.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of the shortage of liver donors, surgical resection remains a safe option in patients with preserved liver functions. 26,30…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Chen et al [25] the RF-assisted liver resection group showed significantly higher serum AST levels than the CUSA group. Other studies have suggested that radiofrequency-assisted hepatectomy without inflow occlusion can prevent ischemia-reperfusion injury of the remnant of the cirrhotic liver and cause only minor liver injury [15,26] . However, the results of the present study indicate that, during liver resection in patients with cirrhosis, radiofrequency ablation involves more damage to the liver function than the Pringle maneuver.…”
Section: Discussionmentioning
confidence: 99%